EFFECTIVENESS OF THE ODD-EVEN NUMBER PLATE TRAFFIC POLICY BASED ON THE REGULATION OF GOVERNOR - Riyanto (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The development of the number of motorized vehicles in Indonesia from 2014 until 2017 has reached 138,556,669 units, the average number of vehicles continues to increase from 6% to 9% per year. The increase in the level of congestion can be felt very significantly. The principal aims of this paper, to evaluate the justification for a national road policy by investigating the Governor of Jakarta Regulation No. 155 of 2018 of its implementations on national roads in Indonesia, especially Jakarta. By looking deeper into the contents of the Articles in Governor of Jakarta Regulation No. 155 of 2018. From this, we will know whether the effectiveness of the Law can discipline highway users with odd-even strategies. The method used in the study is a normative juridical approach to literature and this research was conducted by collecting various literature and secondary data related to the research that will be conducted. The results found that the legal provisions still needed to impose sanctions for violations of the violation of Governor Regulation No. 155 of 2018, meaning that it needs to be reconsidered by the Jakarta Regional Government to make the provisions of separate sanctions outside Article 280.